Caracterização do machado mirense : os materiais de monte dos amantes (Vila do Bispo, Algarve) - Cardoso, João Luís (2015)
The mirian axe is one of the most characteri stic macrolithic artifact from the late Plistocene and/or early post glacial industries of the Baixo Alentejo coast, were it was recognized as a part of a specific industrial assemblage. Initially applied to this particular type of artifact, the mirian designation (from the river Mira estuary, near Vila Nova de Milfontes, took as eponym), is now extended to the whole industrial assemblage. Recent archaeological surveys, at the origin of this study, demonstrated thal the distribution centre of the mirian axc is in fact in the Westem Algarve region. At Monte dos Amantes (Vila do Bispo) were collected more mirian axes.than those from all known sites. Such an important and homogeneous group enabled an essay of typological characterisation, through multivariate statistical methods. A total of fourteen dimensional parameters were considered and expressed numerically and two multivariate factor analysis applied: . ordination by principal component analysis using the PC - programme SPAD; . hierarchive Clustering by the UPGMA method, using the PC - programme NTSYS. The first method allowed the analysis of the Pearson correlations between parameters, showing the homogeneity of the sample in study. The second method allowed the identification of several groups, emphasizing sample size differences, but not morphological variations, because data used was based on dimensional parameters. A new c1uster analysis, by UPGMA was performed. using shape attributes, after an individualisation of fundamental; Sectors, in each artifact. The eight groups obtained showed that, within this statistical homogeneous assemblage, it is possible the identification of several types, perhaps as a result of a funcional speciali sation - like their abundance in this site. This activities, eventually seasonal, of a population that, during the late glacial and/or the first post-glacial times inhabited the littoral and contiguous areas from Baixo Alentejo and Algarve regions, are not yet well known.